Pengaturan Kedudukan Keterangan Saksi dalam Tindak Pidana Kekerasan dalam Rumah Tangga (Regulation on Witness Statements Standing in Criminal Acts of Domestic Violence) - Peter Jeremiah Setiawan; Xavier Nugraha; Ardhana Christian Noventri; Kadek Anda Gangga Putri (Pusat Penelitian Badan Keahlian Setjen DPR RI, 2022)
One thing specific in the criminal acts of domestic violence lies in the provisions of Article 55 of the PKDRT Law. The article requires minimal evidence to prove the defendant’s guilt, which is ample in the form of the victim’s witness statement plus other related evidence. Therefore, when the examination can bring a witness other than the victim’s witness, the testimony of the witness and the testimony of the victim’s witness are considered ample evidence in the trial. However, in its implementation, efforts to strengthen another witness statement as a piece of evidence in the PKDRT Law have not been balanced with complete arrangements, especially with regard to the witness’s evidence, namely the enactment of Article 168 of the Criminal Procedure Code in the PKDRT Law. Based on this background, this study will analyze the position of witnesses in criminal law and the position of witnesses in criminal acts of domestic violence. This study aims to review the role of witness statements in law enforcement against domestic violence crimes and how the law regulates it. The normative legal research method is used to answer these problems. With the increased number of cases of domestic violence that occur every day and the difficulty of collecting evidence to prove the crime of domestic violence, it is necessary to formulate the regulation of witness statements in the crime of domestic violence either through PERMA or the revision of the PKDRT Law. AbstrakSalah satu kekhususan dalam tindak pidana KDRT terletak pada ketentuan Pasal 55 UU PKDRT. Pasal tersebut mensyaratkan minimal alat bukti untuk membuktikan kesalahan terdakwa, yaitu cukup dengan keterangan saksi korban ditambah dengan alat bukti lainnya. Dengan demikian, ketika dalam pembuktian dapat menghadirkan seorang saksi selain saksi korban, maka keterangan saksi dan keterangan saksi korban sudah dianggap sebagai alat bukti yang cukup dalam persidangan. Namun pada implementasinya, upaya penguatan alat bukti saksi dalam UU PKDRT belum diimbangi dengan pengaturan yang lengkap terutama berkaitan dengan alat bukti saksi, yaitu berlakunya Pasal 168 KUHAP dalam UU PKDRT. Berdasarkan latar belakang tersebut, maka tulisan ini akan menganalisis kedudukan saksi dalam hukum pidana dan kedudukan saksi dalamtindak pidana kekerasan dalam rumah tangga. Hal ini bertujuan untuk meninjau peran keterangan saksi dalam penegakan hukum terhadap tindak pidana KDRT dan bagaimana hukum mengatur hal tersebut. Metode penelitian hukum normatif digunakan untuk menjawab permasalahan tersebut. Dengan banyaknya kasus KDRT yang terjadi tiap harinya dan sulitnya pengumpulan alat bukti untuk membuktikan tindak pidana KDRT, maka perlu memformulasikan pengaturan keterangan saksi dalam tindak pidana KDRT baik melalui PERMA maupun revisi UU PKDRT.